2023
DOI: 10.29333/ejmste/13258
|View full text |Cite
|
Sign up to set email alerts
|

Flipped classroom strategies and innovative teaching approaches in physics education: A systematic review

Meiirbek Tunggyshbay,
Nuri Balta,
Wilfried Admiraal

Abstract: More and more educators are adopting the flipped classroom approach (FC) in their teaching, which entails using video-based learning outside of the classroom and interactive group learning activities inside. The aim of this review is to offer a summary of research on the use of flipped classrooms in physics education. A comprehensive analysis of 30 journal publications focusing on flipped classrooms in physics education was conducted. The analysis delved into flipped learning activities and psychological const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In addition to studies stating that quantitative methods are used the most (Chen et. al., 2022;Özbey & Sarıca, 2019;Perez et al, 2023;Tunggyshbay et al, 2023), Özbey and Sarıca (2019) also noted a considerable increase in the use of mixed methods. Köse and Yüzak (2020) reported that quantitative methods were the most common, whereas (Demirer & Aydın, 2007; found that qualitative methods were more prevalent in their studies.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to studies stating that quantitative methods are used the most (Chen et. al., 2022;Özbey & Sarıca, 2019;Perez et al, 2023;Tunggyshbay et al, 2023), Özbey and Sarıca (2019) also noted a considerable increase in the use of mixed methods. Köse and Yüzak (2020) reported that quantitative methods were the most common, whereas (Demirer & Aydın, 2007; found that qualitative methods were more prevalent in their studies.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Rusnilawati et al (2023), in their research in which 193 academic studies conducted at the basic education level were analyzed, stated that the most studies were conducted in 2020 and 2021, the most experimental design research method was used, the most studies were conducted in the USA and then in Spain, and the most studies were conducted with pre-service teachers as the sample level. Tunggyshbay et al (2023) stated that in their research where they examined 30 articles, quantitative research methods and experimental studies were mostly used. Perez et al (2023) stated that most of the studies included in their research used quantitative approaches and that the number of studies on active learning has increased over time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Decision-making must also consider assessment ethics, well-reviewed preparation, and test standardization. Physics education requires hands-on work, such as experiments and problem-solving tasks, but needs more class time for lectures and other instruction forms (Tunggyshbay et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative teaching strategies are needed in the 20 th century (Angraini et al, 2022;Daher et al, 2022a;Retamal Pérez et al, 2023;Tunggyshbay et al, 2023). Since 2021, the implementation of project for improving quality of mathematics and science (PIQMAS) project's teaching strategy has commenced in select schools affiliated with the Palestinian Ministry of Education, specifically in upper basic mathematics and science classes.…”
Section: Introductionmentioning
confidence: 99%